2012
DOI: 10.1515/zfs-2012-0001
|View full text |Cite
|
Sign up to set email alerts
|

Naja, normal und normal. Zur Syntax, Semantik und Pragmatik der x-und-x-Konstruktion im Deutschen

Abstract: This article deals with the syntax, semantics and pragmatics of the x und x ('x and x') construction in German, cf. A: Schade, dass die [Schabracken] so teuer sind! Ϫ B: Naja, teuer und teuer, wenn die Qualität stimmt, dann finde ich den Preis okay. (A: 'What a pity that the horsetrappers are so expensive!' Ϫ B: 'Well, expensive and expensive, if the quality is good, the price is fine with me.'). The specific discourse function of this construction is to negotiate the situational meaning of a previously used l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In contrast to reduplication, however, the rhyming or ablauting conjuncts are generally both lexical words -but the meaning of the coordination phrases is not necessarily compositionally transparent. 8 As a counterpart to frozen coordinations, the "X-and-X-construction" (7) is a coordination of two identical (lexical) words (Finkbeiner 2012, for German).…”
Section: Reduplication and Stem Correspondence Beyond The Word -Lexicmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to reduplication, however, the rhyming or ablauting conjuncts are generally both lexical words -but the meaning of the coordination phrases is not necessarily compositionally transparent. 8 As a counterpart to frozen coordinations, the "X-and-X-construction" (7) is a coordination of two identical (lexical) words (Finkbeiner 2012, for German).…”
Section: Reduplication and Stem Correspondence Beyond The Word -Lexicmentioning
confidence: 99%
“…As the core lexical meaning of the two conjuncts is trivially identical, the contrast is only valid when the specific situational context and the relevant pragmatic meaning are taken into account. That is, the X-and-X-construction is used to "negotiate the situational meaning of a previously used lexical item" (Finkbeiner 2012: 1, and references therein). Interestingly, the X-and-X-construction is a syntactically and prosodically autonomous entity.…”
Section: Reduplication and Stem Correspondence Beyond The Word -Lexicmentioning
confidence: 99%
“…Further, this conversational practice has been attested in Icelandic and Swedish-influenced Estonian (for details, see Lindström & Linell 2007). In a study of German, Finkbeiner (2012) showed that a corresponding pattern ( x-und-x ) occurs in electronic discussion forums, but the construction is not attested in spoken German data. The languages above are Scandinavian or spoken in the Circum-Baltic region, which suggests that this particular reactive construction is an areal phenomenon.…”
Section: Previous Research On the Constructionmentioning
confidence: 99%
“…Also called the "double construction" (Dray 1987;Horn 1993) or "lexical cloning" (Horn 2006;Huang 2015), CR concerns the reduplication of a lexical item to single out a default or prototypical meaning in which one of the duplicates receives contrastive (focal) stress (Ghomeshi et al 2004). CR has been analyzed as head movement into a CR projection (Ghomeshi et al 2004 andsimilarly Travis 2003) and, especially in the German literature, as a word formation process, or to be more precise, as compounding (see, for example, Hohenhaus 2004;Stolz 2009;Finkbeiner 2012;Kentner 2017). In this squib we provide evidence that both accounts, especially the compounding analysis, cannot be correct and instead propose that CR involves phrasal focus movement.…”
Section: Introductionmentioning
confidence: 99%